Potency of Papaya Seed Powder (Carica papaya L.) as Chicken Meat and Shrimp Preservative - Nani Radiastuti; Reno Fitri; Gusniar Berty (UIN Sunan Gunung Djati Bandung, 2020)
Chicken meat and shrimp are perishable food materials. Giving natural preservatives is one way to extend the storage time of food. This study aimed to know the potential of papaya seed powder varieties of ‘Bangkok’ and ‘California’ as preservatives. The sample consisted of two varieties of papaya seed powder with concentrations of 2,4,6 and 8 g. Storage time for chicken meat and shrimp was the third days. Parameters measured were total bacterial colonies, pH va-lues, and organoleptic characteristics (color, aroma and texture) of fresh chicken meat and shrimp. The result showed papaya seed pow-der influences the quality of chicken meat and shrimp. fresh chicken meat and shrimp with papaya seed powder varieties ‘Bangkok’ and ‘California’ had a lower total bacterial colony as much as 9 x 105 until 1x106 compared to control which were 4.2 x 107 - 1.87 x 107. Organoleptic result of chicken meat and shrimp with the treatment of papaya seed powder and stored for three days continue to decrease in term of color, aroma and texture. In chicken meat, the decrease in bacterial growth was still within the limits of microorganism con-tamination quality in animal-based food. However, the same con-centrations of papaya seed powder in the shrimp have not been able to reduce bacterial growth until the limit permitted by SNI.